Constraints on the dynamics and spatio-temporal evolution of the 2011 Oichalia seismic swarm (SW Peloponnesus, Greece) - Kassaras, I.; V. Kapetanidis; A. Karakonstantis; V. Kouskouna; A. Ganas; G. Chouliaras; Drakatos, G.; A. Moshou; V. Mitropoulou; P. Argyrakis; Lekkas, E.; Makropoulos, K. (Tectonophysics, 2014)
In this paper, we present a detailed study of a shallow seismic swarm which took place in the area of Oichalia (SW Peloponnesus), between August and December 2011. The seismic crisis started on 14/8/2011 with an Mw=4.8 earthquake and was followed by more than 1600 events, several of which having magnitude over 4.0. The activity was recorded by local temporary and regional permanent seismic stations. Thousands of records were collected and routinely analyzed. P- and S-wave arrival times were manually picked and incorporated in the HYPOINVERSE algorithm together with a new optimum local velocity model. Hypocentral solutions were improved by applying a double-difference method. Focal mechanisms show that the activated fault zone is dominated by dip-slip normal faulting, trending NNW–SSE, with the average T-axes orientation being N70°E, consistent with regional tectonics. We have investigated towards stress triggering and fluid diffusion, by employing Coulomb stress transfer, spatio-temporal and Frequency–Magnitude Distribution (FMD) analyses. The negligible Coulomb stress transfer and seismicity rate changes that were calculated imply for a stress deficit in the broader study area, hence an external triggering mechanism is required to justify the observed pattern. The b-values increase towards the SSE, compatible with the similarly directed migration of seismicity, showed that the Oichalia swarm could possibly be adapted to an Epidemic Type Aftershock Sequence model (ETAS). Fluid diffusion is reflected in the spatio-temporal hypocenter migration. Clustering analysis, combined with the temporal distribution of b-values, has shown that the swarm evolved in three major phases, the first two being initiated by major events, which were probably triggered externally due to fluid injection that brought the seismogenic volume into a critical state, likely followed by afterslip. The last phase signified a relaxation period, with dispersed seismicity throughout the area and the b-values gently diminishing towards unity.
Keywords: Crustal fluids; Earthquake source; Earthquake swarms; Seismic stress; spatial analysis